Expression of cyanobacterial genes enhanced CO2 assimilation and biomass production in transgenic Arabidopsis thaliana - Anum Zeb Abbasi; Misbah Bilal; Ghazal Khurshid; Charilaos Yiotis; Iftikhar Zeb; Jamshaid Hussain; Ayesha Baig; Mohammad Maroof Shah; Safee Ullah Chaudhary; Bruce Osborne; Raza Ahmad (PeerJ, 2021)
Background Photosynthesis is a key process in plants that is compromised by the oxygenase activity of Rubisco, which leads to the production of toxic compound phosphoglycolate that is catabolized by photorespiratory pathway. Transformation of plants with photorespiratory bypasses have been shown to reduce photorespiration and enhance plant biomass. Interestingly, engineering of a single gene from such photorespiratory bypasses has also improved photosynthesis and plant productivity. Although single gene transformations may not completely reduce photorespiration, increases in plant biomass accumulation have still been observed indicating an alternative role in regulating different metabolic processes. Therefore, the current study was aimed at evaluating the underlying mechanism (s) associated with the effects of introducing a single cyanobacterial glycolate decarboxylation pathway gene on photosynthesis and plant performance. Methods Transgenic Arabidopsis thaliana plants (GD, HD, OX) expressing independently cyanobacterial decarboxylation pathway genes i.e., glycolate dehydrogenase, hydroxyacid dehydrogenase, and oxalate decarboxylase, respectively, were utilized. Photosynthetic, fluorescence related, and growth parameters were analyzed. Additionally, transcriptomic analysis of GD transgenic plants was also performed. Results The GD plants exhibited a significant increase (16%) in net photosynthesis rate while both HD and OX plants showed a non-significant (11%) increase as compared to wild type plants (WT). The stomatal conductance was significantly higher (24%) in GD and HD plants than the WT plants. The quantum efficiencies of photosystem II, carbon dioxide assimilation and the chlorophyll fluorescence-based photosynthetic electron transport rate were also higher than WT plants. The OX plants displayed significant reductions in the rate of photorespiration relative to gross photosynthesis and increase in the ratio of the photosynthetic electron flow attributable to carboxylation reactions over that attributable to oxygenation reactions. GD, HD and OX plants accumulated significantly higher biomass and seed weight. Soluble sugars were significantly increased in GD and HD plants, while the starch levels were higher in all transgenic plants. The transcriptomic analysis of GD plants revealed 650 up-regulated genes mainly related to photosynthesis, photorespiratory pathway, sucrose metabolism, chlorophyll biosynthesis and glutathione metabolism. Conclusion This study revealed the potential of introduced cyanobacterial pathway genes to enhance photosynthetic and growth-related parameters. The upregulation of genes related to different pathways provided evidence of the underlying mechanisms involved particularly in GD plants. However, transcriptomic profiling of HD and OX plants can further help to identify other potential mechanisms involved in improved plant productivity.